A novel and effective method to generate human porcine-specific regulatory T cells with high expression of IL-10, TGF-β1 and IL-35 - Mingqian Li (Nature Portfolio, 2017)
Abstract Organ transplantation remains the most effective treatment for patients with late stage organ failure. Transgenic pigs provide an alternative organ donor source to the limited availability of human organs. However, cellular rejection still remains to be the obstacle for xenotransplantation. Superior to other methods, antigen-specific regulatory T cells (Treg) alleviate cellular rejection with fewer side effects. Here we demonstrate the use of a fast method to provide tolerogenic dendritic cells (tolDC) that can be used to generate effective porcine-specific Treg cells (PSTreg). TolDC were produced within three days from human monocytes in medium supplemented with anti-inflammatory cytokines. Treg were generated from naïve CD4+ T cells and induced to become PSTreg by cocultivation with porcine-antigen-loaded tolDC. Results showed that PSTreg exhibited the expected phenotype, CD4+CD25+CD127low/− Foxp3+, and a more activated phenotype. The specificity of PSTreg was demonstrated by suppression of effector T cell (Teff) activation markers of different stages and inhibition of Teff cell proliferation. TolDC and PSTreg exhibited high expression of IL-10 and TGF-β1 at both protein and RNA levels, and PSTreg also highly expressed IL-35 at RNA levels. Upon restimulation, PSTreg retained the activated phenotype and specificity. Taken together, the newly developed procedure allows efficient generation of highly suppressive PSTreg.